Doxorubicin-Loaded Micelle Targeting MUC1: A Potential Therapeutic for MUC1 Triple Negative Breast Cancer Treatment - Khondee, Supang; Chittasupho, Chuda; Tima, Singkome; Anuchapreeda, Songyot (Current Drug Delivery, 2018)
Background: Triple negative breast cancer (TNBC) is an aggressive disease associated with poor prognosis and lack of validated targeted therapy. Thus chemotherapy is a main adjuvant treatment for TNBC patients, but it associates with severe toxicities. For a better treatment outcome, we developed an alternative therapeutic, doxorubicin (DOX)-loaded micelles targeting human mucin1 protein (MUC1) that is less toxic, more effective and targeted to TNBC. Methods: From many candidate peptides, QNDRHPR-GGGSK (QND) and HSQLPQV-GGGSK (HSQ) were identified computationally, synthesized and purified using solid phase peptide synthesis and semipreparative HPLC. The peptides showed significant high binding to MUC1 expressing cells using a fluorescent microscope. The peptides were then conjugated on pegylated octadecyl lithocholate copolymer. DOX-encapsulated micelles were formed through self-assembly. MUC1-targeted micelles were characterized using dynamic light scattering (DLS) and Transmission Electron Microscopy (TEM). Drug entrapment efficiency was examined using a microplate reader. Cytotoxicity, binding, and uptake were also investigated. Results: Two types of DOX-loaded micelles with different targeting peptides, QND or HSQ, were developed. DOX-loaded micelles were spherical in shape with average particle size around 300-320 nm. Drug entrapment efficiency of untargeted and targeted DOX micelles was about 71-93%. Targeted QND-DOX and HSQ-DOX micelles exhibited significantly higher cytotoxicity compared to free DOX and untargeted DOX micelles on BT549-Luc cells. In addition, significantly greater binding and uptake were observed for QND-DOX and HSQ-DOX micelles on BT549-Luc and T47D cells. Conclusion: Taken together, these results suggested that QND-DOX and HSQ-DOX micelles have a potential application in the treatment of TNBC-expressing MUC1.
Keywords: triple negative breast cancer